2022
DOI: 10.1038/s41467-022-33781-0
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of neurotransmitter identity by Hox proteins through a homeostatic mechanism

Abstract: Hox transcription factors play fundamental roles during early patterning, but they are also expressed continuously, from embryonic stages through adulthood, in the nervous system. However, the functional significance of their sustained expression remains unclear. In C. elegans motor neurons (MNs), we find that LIN-39 (Scr/Dfd/Hox4-5) is continuously required during post-embryonic life to maintain neurotransmitter identity, a core element of neuronal function. LIN-39 acts directly to co-regulate genes that defi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…In C. elegans , Hox genes ceh-13 , lin-39 , mab-5 , and egl-5 are expressed both in developing and adult MNs ( Figure 2 ). 28 , 71 In mice, Hox genes are expressed in developing mouse MNs, 26 , 72 and we found that their expression persists into adulthood ( Figure 6C ). The sustained Hox expression, from embryo to adult, in specific MNs along the rostrocaudal axis points toward non-canonical roles in the adult nervous system.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In C. elegans , Hox genes ceh-13 , lin-39 , mab-5 , and egl-5 are expressed both in developing and adult MNs ( Figure 2 ). 28 , 71 In mice, Hox genes are expressed in developing mouse MNs, 26 , 72 and we found that their expression persists into adulthood ( Figure 6C ). The sustained Hox expression, from embryo to adult, in specific MNs along the rostrocaudal axis points toward non-canonical roles in the adult nervous system.…”
Section: Discussionmentioning
confidence: 70%
“…In C. elegans , combinations of TFs have been described for several neuron types, 30 , 31 , 58 62 but studies of TF function in adult neurons remain rare. 63 In the case of nerve cord MNs, only a handful (e.g., unc-3/EBF , cfi-1/ARID , bnc-1/BNC , mab-9/TBX , lin-39/HOX ) 28 , 64 66 of the 234 TFs we found to be expressed in adult MNs are known to have bona fide roles on adult MN identity and function. This can be addressed by auxin-inducible TF degradation in adult stages to bypass developmental effects caused by constitutive TF alleles.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…UNC-3 and the Hox proteins LIN-39 and MAB-5 are known terminal selectors in C. elegans nerve cord motor neurons. 45 , 46 , 58 , 59 As such, they are continuously required from embryonic to adult stages to activate expression of multiple terminal differentiation genes. 34 , 45 On the other hand, our constitutive (null alleles) and conditional (temporally controlled protein depletion) approaches also revealed a continuous requirement for CFI-1 in motor neurons ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%